Increasing Mental Health Literacy in Law Enforcement to Improve Best Practices in Policing—Introduction of an Empirically Derived, Modular, Differentiated, and End-User Driven Training Design - Lorey, Katharina; Fegert, Jörg M. (Frontiers in Psychiatry, 2021)
Objective: Law enforcement officers often have contact to persons who show symptoms of mental disorders. Adequately designed training is necessary for developing the best possible practices in policing when coming into contact with mentally ill people, and may help to expand their general knowledge on mental disorders. To achieve a sustainable implementation of training content in daily policing work, the acceptance and proactive integration of methods by the training participants is essential. Method: This study investigates an exemplary modular training curriculum based on a survey with 2228 German police officers (28.2 % female, 71.8 % male) concerning their needs and challenges when coming into contact with persons with mental disorders. This empirical end-user driven approach was used to adapt existing training concepts to the current needs and interests of law enforcement personnel in order to maximize compliance. Results: The training program draft includes basic modules which are intended to be of direct interest to all police officers, such as mental disorders with high policing relevance, encountering suicidal patients, (non-directive) communication and de-escalation skills, and mental hygiene in policing. They are arranged in more specialized modules that address specific target group audiences within police forces and the training curriculum provides information about genuine risks and self-protection, trauma sensitivity, and interaction with children and victims among other contents. The self-selectable, modular, and empirically-based continued training program also includes an introduction to local mental health service professionals and networks, trialogue sequences, and situational role play scenarios. Conclusion: Due to frequent contact law enforcement officers have to mentally ill people, improved training designed to maximize knowledge and the integration of trained methods is necessary. Gaining acceptance and proactive support by trainees is ensured through end-user driven implementation of specialized and differentiated up-to-date training programs. Our results showcase how police officers’ perspectives on persons with mental illnesses is a main aspect that can and should be used to encourage training course designs.